Public Service Quality Improvement Strategy by Cirebon City Government Regarding the Granting of Trade-Business-License - Rohadin, R. (Manunggal Halim Jaya, 2021)
This study aims to identify and analyze the strategy to improve trade business licensing (SIUP) services implemented by the Cirebon City Government. The research method used is the descriptive qualitative research method. Data was collected using interviews, observation, documentation, and online data searching techniques. The results of this study indicate that: 1. The quality of SIUP services has been running quite well but not optimal enough when viewed from the dimensions of reliability, physical evidence of service, responsiveness, assurance, and empathy. 2. To improve the quality of SIUP services, BPMPP and the Cirebon City government implement several strategies: core strategy, consequence strategy, customer strategy, control strategy, and cultural strategy. However, the customer strategy still needs to be reformulated because it has not shown satisfactory results. The conclusions of this study are: The quality of SIUP services is still not optimal. This is based on several indicators, e.g., first, In the dimension of reliability, has not been able to meet the timely issuance. Second, in terms of tangibles, the appearance of infrastructure and arrangement of licensing service rooms is quite good; Third, the assurance dimension has provided information certainty starting from the clarity of terms, procedures, and cost certainty.